La Caníbal Mondothèque - Rocha, Jara (Re-visiones, 2024)
Paul Otlet was a bearded man who, from pre-World War II Belgium, worked on the design of a sophisticated knowledge-switching infrastructure or radiated library system which he named "Mundaneum". With an explicitly universalist and therefore Euro-andro-antropocentric perspective, Otlet prototyped the Mondothèque.